2002
DOI: 10.1038/sj.ejhg.5200837
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymorphism in exon 11 of the WKL1 gene, shows no association with schizophrenia

Abstract: A missense mutation in exon 11 of the WKL1 gene on chromosome 22 was found to be associated with cases of catatonic schizophrenia in a single large pedigree. We have screened exon 11 of the WKL1 gene in 174 cases of schizophrenia, including cases of 22 cases of catatonic schizophrenia, but could not detect the previously reported mis-sense mutation. However in exon 11, we observed an insertion/deletion polymorphism, one-missense substitution and two synonymous substitutions. In addition, we also identified a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…1). As previously described [McQuillin et al, 2002], we observed four further polymorphisms (1093C4T, 1111T4C, 1146A4G [N344S], and IVS11-27A4G) in complete linkage disequilibrium with 1165ins33bp in all sequenced PCR templates carrying the insertion. These polymorphisms seem to form a distinct haplotype and we, thus, did not perform further systematic genotyping of these variants.…”
Section: Sequence Variation In Patients With Schizophreniasupporting
confidence: 66%
See 1 more Smart Citation
“…1). As previously described [McQuillin et al, 2002], we observed four further polymorphisms (1093C4T, 1111T4C, 1146A4G [N344S], and IVS11-27A4G) in complete linkage disequilibrium with 1165ins33bp in all sequenced PCR templates carrying the insertion. These polymorphisms seem to form a distinct haplotype and we, thus, did not perform further systematic genotyping of these variants.…”
Section: Sequence Variation In Patients With Schizophreniasupporting
confidence: 66%
“…There was no evidence for genotypic association between the SNPs and schizophrenia. A recently described polymorphism, 1165ins33bp [McQuillin et al, 2002], was found at equal frequency in patients with schizophrenia and controls. The allele frequency of 1165ins33bp was 11.1% (n= 31) among patients with schizophrenia and 15.0% among controls (n= 31; p = 0.15), without evidence for allelic or genotypic association with schizophrenia.…”
Section: Sequence Variation In Patients With Schizophreniamentioning
confidence: 96%
“…The fact that the 1121A allele was not present in any of the 568 Israeli chromosomes tested suggests that his allele is either very rare or does not exist in the Israeli population. Our findings are consistent with two recently published studies that also checked the Leu309Met mutation, as well as 24 SNPs along the WKL1 gene [Devaney et al, 2002;McQuillin et al, 2002]: none of the 24 SNPs (in coding regionsynonymous and -non-synonymous SNPs, and in noncoding regions of the gene), nor the Leu309Met mutation were found to associate with SCZ These data by themselves suggest that the missence mutation Leu309Met is likely to be a neutral polymorphism and not associated with the etiology of SCZ. This is supported by the recent report that the C1121 !…”
Section: Discussionsupporting
confidence: 95%
“…The sixth polymorphism, c.925C4A, has been debated in several works [Devaney et al, 2002;Kaganovich et al, 2004;Leegwater et al, 2002a,b;McQuillin et al, 2002;Meyer et al, 2001;Rubie et al, 2003;Teijido et al, 2004], which describe the possible association of a leucine to methionine change at position 309 with schizophrenia. A recent work reported on the association of schizophrenia and bipolar disorder with MLC1 mutations [Verma et al, 2005].…”
Section: Polymorphismsmentioning
confidence: 99%
“…In a recent series of controls we found that the allelic frequency of the T allele appeared to be 0.21 (n 5 60). The second polymorphism, c.1165ins33, is a very complex rearrangement, involving an imperfect duplication of a 33-bp fragment (Table 2) [Leegwater et al, 2002b;McQuillin et al, 2002;Rubie et al, 2003]. It is present in the heterozygous form in 23% of the individuals in the European population [Rubie et al, 2003].…”
Section: Polymorphismsmentioning
confidence: 99%